Transient 3D CFD Simulation of a Stationary Vane, Oil Free, Rotary Compressor - Farkas, Balázs; Suda, Jenő Miklós (Periodica Polytechnica Mechanical Engineering, 2019)
The evaluation of a newly designed oil-free rotary compressor is presented based on transient 3D Computational Fluid Dynamics (CFD) simulations. The simulations are performed at low compression ratios and low pressure ratios and low rotational speeds. To place the results into context, the data presented in related literature was processed and summarized. The methods related to the CFD model of the newly designed compressor were developed, summarized and evaluated. The accessed CFD data are in good agreement with the results of the former rolling piston compressor related investigations. The oil free operation prevents the contamination of the working fluid from lubricant. Since the compressor is planned to work in open cycle within the sensitive environment of thermal heat sources contamination free operation has to be accomplished. However, oil-free operation also results in significantly lower performance based on the modelling results.